FALLING DOMINOS OR THE ROLE OF GEOGRAPHIC MENTAL MAPS IN FOREIGN POLICY - M. DA VINHA, Luis (European Journal of Geography, 2023)
Geographic mental maps are commonly used to explain foreign policy behaviour of political decision-makers. However, despite the proliferation of their usage, a theoretical account of how mental maps influence foreign policy is still lacking. The current paper seeks to contribute to the development of a theoretical framework which can support the use of mental maps as an analytical concept for foreign policy analysis. Moreover, the paper uses the domino theory as an example to illustrate how geographic cognition and reasoning effectively influence foreign policy.